Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fchem.2023.1160164
|View full text |Cite
|
Sign up to set email alerts
|

From PERK to RIPK1: Design, synthesis and evaluation of novel potent and selective necroptosis inhibitors

Abstract: Receptor-Interacting serine/threonine-Protein Kinase 1 (RIPK1) emerged as an important driver of inflammation and, consequently, inflammatory pathologies. The enzymatic activity of RIPK1 is known to indirectly promote inflammation by triggering cell death, in the form of apoptosis, necroptosis and pyroptosis. Small molecule Receptor-Interacting serine/threonine-Protein Kinase 1 inhibitors have therefore recently entered clinical trials for the treatment of a subset of inflammatory pathologies. We previously id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Recent preclinical and clinical studies have unquestionably recognized the roles of RIPK1 in neurogenerative disorders ( Li & Yuan, 2023 ; Scarpellini et al, 2023 ; Xu, Zhang & Zhuang, 2023 ). In a phase I clinical trial, a small molecule GFH312 showed significant RIPK1 inhibition with a tolerability profile comparable to that of the placebo ( Lickliter et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent preclinical and clinical studies have unquestionably recognized the roles of RIPK1 in neurogenerative disorders ( Li & Yuan, 2023 ; Scarpellini et al, 2023 ; Xu, Zhang & Zhuang, 2023 ). In a phase I clinical trial, a small molecule GFH312 showed significant RIPK1 inhibition with a tolerability profile comparable to that of the placebo ( Lickliter et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%